2020
DOI: 10.3390/ijerph17082968
|View full text |Cite
|
Sign up to set email alerts
|

Patient Opinion of Visiting Therapy Dogs in a Hospital Emergency Department

Abstract: To date there have been no studies examining whether patients want emergency department (ED) therapy dog programs. This patient-oriented study examined the opinions of patients about whether they would want to be visited by a therapy dog in the Royal University Hospital ED. Cross-sectional survey data were collected over a six week period from a convenience sample of 100 adult patients who had not been visited by a therapy dog in the ED. Most (80%) indicated they would want a visit by a therapy dog as an ED pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…(Beck, 2014;Kline et al, 2019) Recent studies also suggested that therapy dogs are more accepted by the community, especially for people who have domestic pets or have experience with them. (Reddekopp et al, 2020) Only a small number of patients and hospital staff are afraid or are concerned that therapy animals may pose a sanitary risk. (Kline et al, 2019;Nahm et al, 2012) There are several major contraindications of AAT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Beck, 2014;Kline et al, 2019) Recent studies also suggested that therapy dogs are more accepted by the community, especially for people who have domestic pets or have experience with them. (Reddekopp et al, 2020) Only a small number of patients and hospital staff are afraid or are concerned that therapy animals may pose a sanitary risk. (Kline et al, 2019;Nahm et al, 2012) There are several major contraindications of AAT.…”
Section: Resultsmentioning
confidence: 99%
“…Despite researchers challenging the methodology of proving the effectiveness of AAT, the therapy should be performed along with usual treatments when the potential risk of any adverse effect is low. (Reddekopp et al, 2020) Art therapy Art therapy is considered a form of creative therapy. It is utilized to treat psychological disorders and to improve the patient's mental wellbeing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A case study by Dell et al [ 24 ] of patients in a Canadian ED revealed that visiting with a therapy dog improved patients’ perceived levels of comfort and distress and it was a welcome distraction for patients from a stressful ED environment. These same authors surveyed patients waiting in an ED about whether they would want to be visited by a therapy dog, and the vast majority agreed and were of the opinion that patients may want to visit with a therapy dog “to reduce anxiety (92%) and frustration (87%) as well as to increase comfort (90%) and satisfaction (90%) and to a lesser extent to reduce pain (59%)” [ 27 ].…”
Section: Introductionmentioning
confidence: 99%